Synthesis and fluorescence properties of a full set of extended RNA base analogues - Sabale, Pramod M.; Nuthanakanti, Ashok; Srivatsan, Seergazhi G. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2013)
The synthesis and photophysical characterization of a complete set of fluorescent RNA base analogues derived by conjugating benzofuran moiety at the 5- and 8-positions of pyrimidine and purine bases, respectively, are described. Benzofuran-modified pyrimidine and purine ribonucleoside analogues exhibit Contrasting fluorescence properties. Pyrimidine analogues are moderately emissive with emission maximum in the visible region, and importantly, are highly sensitive to solvent polarity and Viscosity changes. On the other hand, purine analogues are highly emissive and are minimally affected by solvation. and viscosity effects. Thorough photophysical analysis reveals that the pyrimidine and purine ribonucleosides displaying distinct and-probe-like fluorescence properties could be useful in designing nucleic acid based biophysical tools to study nucleic acid structure and function.
Keywords: Environment sensitive probes; Fluorescence probes; Fluorescence spectroscopy; Nucleic acids; Ribonucleoside analogues

Self-assemblies of nucleolipid supramolecular synthons show unique self-sorting and cooperative assembling process - Nuthanakanti, Ashok; Walunj, Manisha B.; Torris, Arun; Badiger, Manohar V.; Srivatsan, Seergazhi G. (Nanoscale, 2019)
The inherent control of the self-sorting and co-assembling process that has evolved in multi-component biological systems is not easy to emulate in vitro using synthetic supramolecular synthons. Here, using the basic component of nucleic acids and lipids, we describe a simple platform to build hierarchical assemblies of two component systems, which show an interesting self-sorting and co-assembling behavior. The assembling systems are made of a combination of amphiphilic purine and pyrimidine ribonucleoside-fatty acid conjugates (nucleolipids), which were prepared by coupling fatty acid acyl chains of different lengths at the 2 `-O- and 3 `-O-positions of the ribose sugar. Individually, the purine and pyrimidine nucleolipids adopt a distinct morphology, which either supports or does not support the gelation process. Interestingly, due to the subtle difference in the order of formation and stability of individual assemblies, different mixtures of supramolecular synthons and complementary ribonucleosides exhibit a cooperative and disruptive self-sorting and co-assembling behavior. A systematic morphological analysis combined with single crystal X-ray crystallography, powder X-ray diffraction (PXRD), NMR, CD, rheological and 3D X-ray microtomography studies provided insights into the mechanism of the self-sorting and co-assembling process. Taken together, this approach has enabled the construction of assemblies with unique higher ordered architectures and gels with remarkably enhanced mechanical strength that cannot be derived from the respective single component systems.

Terminal uridylyl transferase mediated site-directed access to clickable chromatin employing CRISPR-dCas9 - George, Jerrin Thomas; Azhar, Mohd; Aich, Meghali; Sinha, Dipanjali; Ambi, Uddhav B.; Maiti, Souvik; Chakraborty, Debojyoti; Srivatsan, Seergazhi G. (Journal of the American Chemical Society, 2020)
Locus-specific interrogation of target genes employing functional probes such as proteins and small molecules is paramount in decoding the molecular basis of gene function and designing tools to modulate its downstream effects. In this context, CRISPR-based gene editing and targeting technologies have proved tremendously useful, as they can be programmed to target any gene of interest by simply changing the sequence of the single guide RNA (sgRNA). Although these technologies are widely utilized in recruiting genetically encoded functional proteins, display of small molecules using CRISPR system is not well developed due to the lack of adequate techniques. Here, we have devised an innovative technology called sgRNA-Click (sgR-CLK) that harnesses the power of bioorthogonal click chemistry for remodeling guide RNA to display synthetic molecules on target genes. sgR-CLK employs a novel posttranscriptional chemoenzymatic labeling platform wherein a terminal uridylyl transferase (TUTase) was repurposed to generate clickable sgRNA of choice by site-specific tailoring of multiple azide-modified nucleotide analogues at the 3' end. The presence of a minimally invasive azide handle assured that the sgRNAs are indeed functional. Notably, an azide-tailed sgRNA targeting the telomeric repeat served as a Trojan horse on the CRISPR-dCas9 system to guide synthetic tags (biotin) site-specifically on chromatin employing copper-catalyzed or strain-promoted click reactions. Taken together, sgR-CLK presents a significant advancement on the utility of bioorthogonal chemistry, TUTase, and the CRISPR toolbox, which could offer a simplified solution for site-directed display of small molecule probes and diagnostic tools on target genes.